Study on the mechanism of carbide precipitation by surface quenching treatment on GCr15 bearing rings based on the phase-field method - Liu, Qian; Jiang, Jiaxuan; Chen, Ming; Deng, Xiaohu; Wang, Jiangang; Ju, Dongying (Frontiers in Materials, 2022)
In this paper , it has adopted the thermodynamics database which is Gibbs free energy of phase and M23C6 phase based on Fe-Cr-C ternary alloy , coupled macro numerical simulation results of quenching in heat treatment simulation software COSMAP , and developed a phase field model on the mesoscopic scale which simulates precipitation , growth and coarsening of M23C6 carbides in FCC austenitic matrix by considered elastic energy . The model has calculated M23C6 carbides aspects of phase composition , element distribution , evolution included nucleation, growth and coarsening in quenching process of GCr15 bearing ring . By means of comparison between the calculation results of phase field method and the morphology , quantity and distribution of carbides observed by SEM experiment , this study presented mechanism on precipitation of micro M23C6 carbides influenced by quenching process parameters , verified the rationality of the phase field model developed and the feasibility of M23C6 carbides precipitation mechanism used by phase field simulation method .